BUSINESS INTELLIGENCE SYSTEMS IN SUPPORT OF CORPORATE FINANCIAL POLICY FOR SMES - Rostek, Katarzyna (Acta Scientiarum Polonorum. Oeconomia, 2010)
SMEs are increasingly interested in tools supporting business analytics, including the ability to support of company’s financial policy management. Business Intelligence technology is one of the solutions, that can successfully be used in this area. Ability to integrate the available data, the realization of any financial analysis, automation of financial reporting and interactive visualization the obtained results are an indispensable part of effective company’s financial policy management. In the theoretical part the article focuses on Business Intelligence solutions, and in particular on those aspects of their operation, which support the financial policy management of a company. In the research part of the article is presented a comparative analysis of selected Business Intelligence tools and possibility of their use to support financial analysis and the availability of SME companies. There were selected the tools of: BI market leading suppliers, who have offered software dedicated to SMEs (group I – market leaders BI), vendors modern and innovative solutions appeared on the BI market (group II – BI market visionaries) and suppliers open source BI (group III – OSBI). The products were evaluated in terms of: availability for SME businesses, opportunities for integration with existing IT environment, the scope of support for the company’s financial policy and modernity of solutions. Obtained analyzing results allow to conclude that the selection of the best BI solution, supporting the management’s financial policies for SMEs, must be preceded by careful analysis of needs and capacity of the enterprise with respect to functionality and price of BI systems, available on the market.